Analisis Fundamental dan Kebijakan Dividen: Peran Moderasi Pertumbuhan Laba Pada Industri Perbankan di Indonesia - Saputra, Praja Hadi; Kusumawati, Yulia Tri (Jurnal Ilmiah Poli Bisnis, 2022)
This aims of this study is to assess the influence of financial ratios as a fundamental analysis on dividend policy and also investigate the moderating role of profit growth between the relationship. Research samples were banking industry listed on IDX in 2017 to 2019 and selected using purposive sampling. Structural Equation Modeling (SEM - PLS) used in this study as the statistical tools for data analysis. The results indicated that only Liquidity and Profit Growth have a significant effect on Dividend Policy. Contradiction, profitability and capital structure have no influence on Dividend Policy. The moderating effect of profit growth on the relationship between profitability, liquidity, and capital structure and dividend policy indicate that profit growth has a moderating role on the relationship between profitability and dividend policy. However, it did not moderate the relationship between liquidity and capital structure on dividend policy in the Indonesian banking industry.